THE ROLE OF ASN SIMPONI ON WORKERS DISCIPLINE AND PERFORMANCE AT DEPARTMENT OF TRANSPORTATION, SOUTH EAST SULAWESI PROVINCIAL (THE INVOLVEMENT OF DIRECT SUPERVISORSHIP) - Satyadharma, Maudhy; Suhri Kasim, Syaifudin (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
This study aims to look at, describe and analyze (1) the implementation of the policy for implementing the Simponi ASN Application to the Department of Transportation, Southeast Sulawesi Provincial ASN, and (2) the impact of implementing the policy for implementing the Simponi ASN Application on ASN discipline and performance with the involvement of direct supervisor supervision. This type of research is descriptive research with a qualitative approach. Research with a qualitative description method is used so that researchers can explain more deeply and comprehensively about the description of cases that occur in the field. Research has been carried out in Kendari City in December 2024-February 2025. The results of the study concluded that (1) the implementation of the Simponi ASN Application policy implementation has been running in terms of indicators of policy size and objectives, resources, characteristics of implementing agents, attitudes or tendencies of implementers, inter-organizational communication and implementing activities and the environment economic, social and political. And (2) the implementation of the Simponi ASN Application policy has an impact on the discipline and performance of ASN which is supported by the supervision of the direct supervisor.